Preparation and Characterization of Fluorone Ligand Complexes for Co+2, Mn+2, and Fe+2 Metallic Ions - ahmed Salem; Hameed Ali; Omar Al-Obaidi (مجلة جامعة الانبار للعلوم الصرفة, 2023)
In this study, new complexes are produced by bonding of transition metal dinuclear chlorides (CoCl2.6H2O, MnCl2.4H2O, and FeCl2.6H2O) with a polychelated ligand called 9-Phenyl-2,3,7-trihydroxy-6-fluorone, represented by (L), in a 1:2 (metal: ligand) ratio. Applying the appropriate chemical and physical methods, such as melting points, molar electrical conductivity, magnetic sensitivity, FT-IR, UV-Visible, and mass spectrometric studies, the produced complexes were characterized. All complexes are non-electrolytic, according to analyzes of molar electrical conductivity. All complexes have an octahedral structure, according to studies of magnetic sensitivity and Uv-Visible spectra. The mass spectrometry measurements showed the presence of the molar mass bands of the complex and the appearance of other bands resulting from the fragmentation of the complexes. For the metallic complexes spectra, FT-IR revealed a shift in the shape and intensity of the complexes bands at lower frequencies. The bonding of the metal to the oxygen atom can be observed by this shift in the bond stretch of the ligands. The size of the coordination between the ligand and the ions of the metallic elements is the cause. The measurement of the complexes' melting point is high, which suggests that the resultant complexes are quite stable.